Behavioral theory-based framework for prediabetes self-care systemdesign perspectives and validation results - Subramaniam S.; Dhillon J.S.; Wan Ahmad W.F. (MDPI, 2023)
glucose; diabetes; disease control; empowerment; health care; lifestyle; adult; Article; attitude to health; behavior change; behavior theory; conceptual framework; controlled study; empowerment; feasibility study; female; glucose blood level; health behavior; health care management; health care planning; human; i PreventDiabetes system; impaired glucose tolerance; lifestyle; lifestyle modification; major clinical study; male; medical informatics; middle aged; motivation; non insulin dependent diabetes mellitus; nutrition; patient attitude; patient monitoring; physical activity; prophylaxis; qualitative research; quantitative study; self care; study design; validation study; impaired glucose tolerance; non insulin dependent diabetes mellitus; self care; Diabetes Mellitus, Type 2; Humans; Life Style; Motivation; Prediabetic State; Self Care